2020
DOI: 10.1002/tox.22998
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐122‐5p and miR‐326‐3p promote cadmium‐induced NRK‐52E cell apoptosis by downregulating PLD1

Abstract: Cadmium is a toxic heavy metal distributed broadly in the environment and manufactory industry. Long‐term exposure to cadmium, considered as a risk for kidney injury, leads to chronic kidney disease eventually. Phospholipase D1 (PLD1) promotes cell proliferation and inhibits apoptosis, and might be involved in cadmium‐induced kidney injury. In this study, we used miRNA microarray assays and bioinformatics analysis to identify miRNAs, which may regulate PLD1 expression and exert an impact on cadmium‐induced kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Aberrant apoptosis, a typical characteristic in the epithelial layer of OLP, impairs the integrity of oral epithelia barrier against bacteria 28,29 . In this study, we verified that miR‐122 overexpression leads to excess cell apoptosis in HOKs, which is in accordant with previous observations indicate that miR‐122 regulates apoptosis in various cell types and diseases 26,27 . In addition, consistent with early reports, 24 substantial TUNEL‐stained oral keratinocytes were observed in the specimens from OLP patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Aberrant apoptosis, a typical characteristic in the epithelial layer of OLP, impairs the integrity of oral epithelia barrier against bacteria 28,29 . In this study, we verified that miR‐122 overexpression leads to excess cell apoptosis in HOKs, which is in accordant with previous observations indicate that miR‐122 regulates apoptosis in various cell types and diseases 26,27 . In addition, consistent with early reports, 24 substantial TUNEL‐stained oral keratinocytes were observed in the specimens from OLP patients.…”
Section: Discussionsupporting
confidence: 92%
“…Up‐regulation of miR‐122 induces cell apoptosis in oral keratinocytes. MiR‐122 is able to regulate cell apoptosis in a variety of cell types 26,27 . To better understand the role of miR‐122 in apoptosis of oral keratinocytes, we treated HOKs with miR‐122 mimics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium (Cd), a toxic heavy metal, could be accumulated in human bodies through drinking water, foods, occupational exposure, and so on 1 . Previous reports have demonstrated that Cd could induce oxidative stress, DNA damage, apoptosis, and mitophagy 2–4 . More importantly, a vast majority of studies have reported that Cd could promote cell proliferation in many cancer cells 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 26 In addition, miR‐326‐3p enhances cadmium‐triggered NRK‐52E cell apoptosis via down‐regulating PLD1. 27 Here, miR‑326‐3p was down‐regulated in VSMCs treated with ox‐LDL and it was negatively modulated by circ_0002984. Next, overexpression of miR‑326‐3p reversed the circ_0002984 overexpressing‑induced effects on the viability, migration and inflammation of VSMCs.…”
Section: Discussionmentioning
confidence: 85%